The implementation of a code of ethics: The early efforts of one entrepreneur - Oliverio, Mary Ellen (Journal of business ethics, 1989)
Attention is being focused on the ‘tone at the top’ in businesses in the United States with the publication of the Report of the Commission on Fraudulent Financial Reporting. There has been growing discontent with the quality of ethcial behavior in the business society and at the present moment many American companies are developing — or revising — codes of ethics and establishing procedures for their implementation. Yet, there is some question about the success of such efforts., This article describes the efforts of an early American entrepreneur to develop a code of ethics and to implement it throughout his organization during the early years of relatively rapid growth. The code was introduced in 1913 and was supported through a variety of means in which the leader himself participated. That early code continues to be reissued as the company updates its overall code of ethics. The persistent and seemingly genuinc commitment to ethical behavior throughout the company was evident in all aspects of the leader's behavior.